"واقع استخدام سلسلة القيمة كأداة لتحليل الاستراتيجي للبيئة الداخلية" - حنان, بوصبيع صالح; سارة, مليك (University of eloued جامعة الوادي, 2021)
"تهدف هذه إلى دراسة إلي اكتشاف مدى واقع تطبيق المؤسسات الاقتصادية بولاية الوادي لسلسلة القيمة كأداة لتحليل لاستراتيجي للبيئة الداخلية، وكذلك إظهار مدى فعاليته في تحقيق ميزة تنافسية للمؤسسات التي تستخدمها . تمت الدراسة من خلال محاولة الإجابة على الإشكالية الرئيسية التالية: إلى أي مدى تلتزم المؤسسات الاقتصادية بتحليل سلسلة القيمة كوسيلة لتحليل البيئة الداخلية؟ تم معالجة الموضوع من خلال شقين أحدهما نظري وآخر تطبيقي، من خلال اعتماد على المنهج استقرائي ففي الجانب النظري تم التعرف على ماهية التحليل لاستراتيجي وكدا التحليل الاستراتيجي للبيئة الداخلية وسلسلة القيمة، كما تم التطرق إلى كي استفادت من سلسلة القيمة كأداة لتحليل البيئة الداخلية للمؤسسة؛ أما في الجانب التطبيقي فقد تم إسقاط المعارف النظرية على الواقع العملي باستخدام المنهج الوصفي التحليلي. تمثلت أداة الدراسة في استبيان موزع على عينة من 50فرد من مسيرين لمؤسسات اقتصادية في ولاية الوادي وكذلك لمعالجة إشكالية الموضوع واختبار فرضياته تم الاعتماد على التحليل الإحصائية وبرنامج .SPSS ،V22وقد تم التوصل إلى أن هناك درجة عالية من الوعي بأهمية تبني سلسلة القيمة كما يوجد توجه بدرجة عالية نحو تعزيز ممارسات سلسلة القيمة ضمن أداة لإنشاء قيمة لوظائفها ومنتجتها وتخفيض التكالي ،كما تواجه هده المؤسسات لجملة من التحديات في سبيل استخدامها لسلسلة القيمة من أهمها التكلفة الاقتصادية للسلسلة القيمة.""This study aims to explore the extent to which economic institutions in the Valley State apply value chain as a tool for strategic analysis of the internal environment ، as well as to demonstrate its effectiveness in achieving a competitive advantage for the enterprises they use. The study was carried out by attempting to answer the following major problem: to what extent are economic institutions committed to value chain analysis as a means of analysing the internal environment? The topic was addressed in two theoretical and applied parts. In the theoretical aspect ، the analysis was identified as strategic and the strategic analysis of the internal environment and value chain and how it has benefited from the value chain as a tool to analyse the enterprise's internal environment; On the applied side ، theoretical knowledge was dropped on practical reality using the analytical descriptive curriculum. The study tool was a questionnaire distributed to a sample of 50 individuals from economic enterprises in the Valley State as well as to address the issue and test its hypotheses. The statistical analysis and the spssvprogramme were based on the study's analysis. and it has been found that there is a high degree of awareness of the importance of adopting the value chain and that there is a high tendency to promote value chain practices within a tool to create value for its functions and product and reduce costs Institutions also face a number of challenges in using the value chain ، the most important of which is the economic cost of the value chain"
ماستر اقتصاد
Keywords: تحليل البيئة الداخلية، سلسلة القيمة، تحليل سلسلة القيمة; internal environment analysis ، value chain ، Value Chain Analysis